De las políticas públicas a las prácticas educativas: la incidencia de la práctica del supervisor escolar - Vercellino, Soledad; Enrico, Liliana (Revista Complutense de Educación, 2006)
The supervisor is one of the state tools to the control of the execution of the establishment of rules and regulations that constitute the educative policy, playing –sometimes– some role on its beginning. This put the supervisor’s position in tension because It is situated in the intersection of two different force’s configurations, with their own rules each one: the high public-educative function and the local conformation. In this frame, the supervisors fight against other agents to meet the usufruct of the technical competence to know and take part in the performance of the scholastic institutions and in the developing of educative policy. This article analyse which have been the position taken by the Scholastic Supervisor, in the frame of the educative policy of Río Negro province (1991-2003) and the strategies that they developed.